11th EAD Conference Proceedings: The Value of Design Research 2016
DOI: 10.7190/ead/2015/174
|View full text |Cite
|
Sign up to set email alerts
|

Please Mind the Balance. Using Design to Engage Households in the Smart Grid Scenario

Abstract: In the future Smart Grid scenario, load balancing is considered one opportunity to cut the peaks on the electrical grid, in order to reduce the negative effects of electricity production on environment. Load balancing can be performed by households, who actively shift their electricity-consuming activities to reduce peaks. Therefore, household customers need to become "active" concerning their electricity use. As smart grids are implemented into society, there is an increasing need to know how the transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The process led to very different designs of information in relation to load management than suggested by [2,3,7]. For a full account of the design process, we followed a complete description of the final design of the Peacetime prototype [10,25].…”
Section: Design Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The process led to very different designs of information in relation to load management than suggested by [2,3,7]. For a full account of the design process, we followed a complete description of the final design of the Peacetime prototype [10,25].…”
Section: Design Approachmentioning
confidence: 99%
“…The previously mentioned pre-study [10] informed the design of the probe. Through a participatory design process, designers, researchers, and end users were engaged in ideation sessions, conceptualization workshops, and focus groups to inform and enrich the development of the design.…”
Section: Design Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be a lack of understanding the resistance to households engaging in load balancing. Although studies have indicated that people believe themselves to be quite flexible in their use of electricity, some activities might be non-negotiable in respect of the hours during the day they would be performed [23]. Shifting activities would involve a certain amount of planning and require information in advance about the periods of the day, during which they should avoid using electricity and how long that period would be.…”
Section: Introductionmentioning
confidence: 99%